Mundo contemporâneo e adoecimento: considerações sobre as LER/DORT - Evangelista, Vitor Moraes Alves [UNESP]; Kadooka, Aline [UNESP]; Schmidt, Maria Luiza Gava [UNESP]; Lucca, Sergio Roberto de (My University, 2013)
With the advent of the industrial revolution, the sickening resulted from labor and work raised significantly, and Work Related Musculoskeletal Disorders (WRMD) emerged as one of the main aggravation to the worker’s health. The present article has as its objectives, through a bibliographical revision about this theme, to sketch the contemporary world of work and labor, bringing to surface the principle aspects that constitute and hide the reality of its labor context in which the workers are inserted and then, to do an analysis about the importance of the psychosocial factors in the genesis of the WRMD symptoms.

Com o advento da revolução industrial, o adoecimento decorrente do trabalho aumentou de forma significativa, e os Distúrbios Osteomusculares Relacionados ao Trabalho (DORT) emergiram como um dos principais agravos à saúde do trabalhador. O presente artigo teve como objetivo, através de uma revisão bibliográfica sobre o tema, esboçar o mundo contemporâneo do trabalho, trazendo à tona os principais aspectos que constituem e ocultam a realidade do contexto laboral na qual os trabalhadores estão inseridos e, a partir de então, fazer uma análise sobre a importância dos fatores psicossociais na gênese dos sintomas das DORT.
Contemporary world of work and illness: considerations RSI/WMSDS
Keywords: Work; Psychosocial factors; Work Related; Musculoskeletal Disorders; Abordagem psicológica e social; Aspectos psicológicos; Disturbios osteomusculares